Paul Diracs view of the Theory of Elementary Waves - Boyd, Jeffrey (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Is science open to a new idea? Thomas Kuhn says paradigm shifts sound like gibberish to scientific leaders, and are rejected for that reason. The Theory of Elementary Waves (TEW) is such an idea: quantum particles follow waves moving in the opposite direction. Time always goes forwards. We focus on Paul Diracs 1930 book The Principles of Quantum Mechanics, applied to TEW. We keep Dirac notation and quantum math but replace the picture of how nature is organized. Wave interference and probabilistic effects occur prior to particle emission. Wave function collapse occurs at emission & there is no further interference. We have launched a successful program of teaching this form of physics in the format of YouTube music videos of five minutes duration. Some of our videos have been watched 40,000 times: within YouTube search for Jeffrey H Boyd to watch these amusing videos including one in which Yoda (from Star Wars) solves what Richard Feynman called the Fundamental Mystery of Quantum Mechanics.